Unsteady MHD flow due to non-coaxial rotations of a porous disk and a fluid at infinity subjected to a periodic suction - Guria, M. (Zielona Góra: Uniwersytet Zielonogórski)
The unsteady flow of a viscous incompressible electrically conducting fluid due to non-coaxial rotations of a porous disk subjected to a periodic suction and the fluid at infinity in the presence of applied transverse magnetic field has been studied. The fluid at infinity passes through a fixed point. The velocity field, shear stresses are obtained in a closed form.
Keywords: Hall currents; eccentric; MHD; oscillating; rotating